Germline prediction of immune checkpoint inhibitor discontinuation for immune-related adverse events - Min Li; Geoffrey Liu; Elad Ziv; Rohit Thummalapalli; Adam Schoenfeld; Melinda C Aldrich; Scott Huntsman; Zoe Quandt; Christine M Lovly; Pooja Middha; Karmugi Balaratnam; Eduardo Cardenas; et al. (Journal for ImmunoTherapy of Cancer)
Introduction Immune checkpoint inhibitors (ICIs) can yield remarkable clinical responses in subsets of patients with solid tumors, but they also commonly cause immune-related adverse events (irAEs). The predictive features of clinically severe irAEs leading to cessation of ICIs have yet to be established. Given the similarities between irAEs and autoimmune diseases, we sought to investigate the association of a germline polygenic risk score for autoimmune disease and discontinuation of ICIs due to irAEs.Methods The Genetics of immune-related adverse events and Response to Immunotherapy (GeRI) cohort comprises 1302 patients with non-small cell lung cancer (NSCLC) who received ICI therapy between 2009 and 2022 at four academic medical centers. We used a published polygenic risk score for autoimmune diseases (PRSAD) in the general population and validated it in the All of Us. We then assessed the association between PRSAD and cessation of ICI therapy due to irAEs in the GeRI cohort, using cause-specific and Fine-Gray subdistribution hazard models. To further understand the differential effects of type of therapy on the association between PRSAD and cessation of ICI due to irAEs, we conducted a stratified analysis by type of ICI therapy.Results Using a competing risk model, we found an association between PRSAD and ICI cessation due to irAEs (HR per SD=1.24, p=0.004). This association was particularly strong in patients who had ICI cessation due to irAEs within 3 months of therapy initiation (HR per SD=1.40, p=0.005). Individuals in the top quintile of PRSAD had 4.8% ICI discontinuation for irAEs by 3 months, compared with 2% discontinuation by 3 months among patients in the bottom quintile (log-rank p=0.03). In addition, among patients who received combination programmed cell death protein-1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors and cytotoxic T-lymphocyte associated protein 4 (CTLA4) inhibitors, ICI discontinuation for irAEs by 3 months occurred in 4 of the 13 patients (30.8%) with high PRSAD genetic risk (top quintile) versus 3 of 21 patients (14.3%) with low PRSAD genetic risk (bottom quintile).Conclusions We demonstrate an association between a polygenic risk score for autoimmune disease and early ICI discontinuation for irAEs. Our results suggest that germline genetics may be used as an adjunctive tool for risk stratification around ICI clinical decision-making in solid tumor oncology.